FREEDOM OF SPEECH AS A CONSTITUTIONAL RIGHT: A REVIEW OF DEMONSTRATION HANDLING PRACTICES - Asep Sapsudin (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
This study aims to analyze the legal guarantees of the principle of non-discrimination in fulfilling the voting rights of people with disabilities in general elections in Indonesia and to identify technical obstacles to its implementation in the field. The right to vote is a constitutional right of citizens that must be fulfilled without exception. This study uses a normative legal research method with a statute approach and a conceptual approach. Secondary data sourced from primary, secondary, and tertiary legal materials are analyzed qualitatively and descriptively. The results show that normatively, Indonesia has a strong and multi-layered legal framework, starting from the 1945 Constitution, ratification of the Convention on the Rights of Persons with Disabilities (CRPD), and the Election Law, which mandates affirmative policies for people with disabilities. However, at the empirical level, technical implementation at Polling Stations (TPS) still faces serious obstacles. These obstacles include the lack of physical accessibility for wheelchair users, limited voting aids (braille templates), the absence of visual communication media for deaf voters, inaccurate data on the Permanent Voters List (DPT), and the low sensitivity of KPPS officers. The conclusion of this study emphasizes the need for standardization and audit of TPS accessibility, reform of the technical guidance curriculum for organizers through disability awareness training, and strengthening synergy with organizations of people with disabilities in order to realize inclusive and fair elections.